New technique for direct targeting of the ventral intermediate nucleus using magnetic resonance-guided focused ultrasound - Aibar-Duran, Juan Ángel; Akira Watanabe, Rodrigo; McDannold, Nathan J.; Cosgrove, G. Rees (Frontiers in Radiology, 2025)
BackgroundAccurate targeting and lesion placement are critical in treating movement disorders with magnetic resonance-guided focused ultrasound (MRgFUS). Indirect atlas-based targeting often lacks precision. Direct anatomical targeting with 3T MRI offers a promising alternative. This report aims to refine MRgFUS thalamotomy by integrating advanced imaging and lesion conformality strategies.Material and methodsPreoperative and postoperative white matter null (WMn) MR-imaging was employed for direct Vim detection. Essential anatomical landmarks are identified. Dual-lesion conformality was used to adapt to the spatial distribution of the Vim.ResultsLesions of the Vim were identifiable using the postoperative WMn MRI sequence. The direct visualization of the Vim usually avoids extension into the internal capsule and the sensory thalamic nucleus. Sagittal imaging confirmed the dual-lesion conformational strategy which conforms to the antero-superior orientation of the Vim.ConclusionsDirect Vim targeting for MRgFUS is feasible for individual cases with the use of WMnMPRAGE MRI sequences. The use of lesion conformality adapts well to the anatomical and spatial distribution of Vim. Further studies will be needed to confirm the safety profile of this approach and correlate with clinical outcomes.